Rehabilitation of mentally retarded children - TR, Shukla (Journal of All India Institute of Speech and Hearing, 1972)
Mentally Retarded are those unfortunate persons, whose mental growth is arrested or incomplete. These individuals have been posing problems to society in various ways and society has been trying to help them in order to help itself. Much has been done for them in advanced countries, but very little has been done in India. There are many aspects of the problem such as classification, causes, prevention and treatment, etc.